Handbook of Spectrum Auction Design
DOI: 10.1017/9781316471609.006
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Auction Design

Abstract: Combinatorial auctions allow for more expressive bidding in which participants can submit package bids with logical constraints that limit allowable outcomes. This type of auction can be useful when participants' values are complementary or when participants have production and financial constraints. However, combinatorial auctions are currently rare in practice. The main problems confronted in implementing these auctions are that they have computational uncertainty (i.e., there is no guarantee that the winnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Pikovsky (2008) compared three selected linear price auction designs and the Vickrey-Clark-Groove auction using computer simulations and laboratory experiments. The selected auction designs are Clock Combinatorial auctions (Porter et al 2003), the RAD, and the author's own design, called ALPS. He observed that the auction designs performed very well for different value models even in the case of valuations that exhibit high synergy levels, although there are significant differences in the efficiency and revenue distributions of the evaluated designs.…”
Section: Simulation Frameworkmentioning
confidence: 99%
“…Pikovsky (2008) compared three selected linear price auction designs and the Vickrey-Clark-Groove auction using computer simulations and laboratory experiments. The selected auction designs are Clock Combinatorial auctions (Porter et al 2003), the RAD, and the author's own design, called ALPS. He observed that the auction designs performed very well for different value models even in the case of valuations that exhibit high synergy levels, although there are significant differences in the efficiency and revenue distributions of the evaluated designs.…”
Section: Simulation Frameworkmentioning
confidence: 99%
“…Each round is time restricted by the auctioneer, so each player has to place a bid before the end of the round; otherwise the bid is not considered valid. Finally, since the proposed auction is (semi-)combinatorial, package bidding is allowed [34] and is justifiably profitable for both seller and buyer.…”
Section: A Model Desccriptionmentioning
confidence: 99%
“…In the context of our auction scheme, this means that the auction favors big players who bid for big packages of sub-projects. The threshold problem was mitigated by FCC by introducing the Combinatorial Clock (CC) [34], an auction type where the initial price is determined by the auctioneer and where the bidders express only their interest to purchase specific assets or packages at the current price. The prices rise automatically by a clock, as long as a bidder expresses her interest for an asset or packages.…”
Section: B Advantages and Limitationsmentioning
confidence: 99%
“…Besides efficiency, CAs provide lower transaction costs and higher transparency [9]. A well-chosen auction format ensures a time-saving and efficient negotiation process when dealing with complex goods and consequently reduces transaction costs.…”
Section: Advantages Of the Combinatorial Auctionmentioning
confidence: 99%
“…The most prominent mechanism is the Generalized Vickrey Auction by Varian and MacKieMason [15], which is based on the Vickrey-Clarke-Groves (VCG) mechanism [16]. The VCG mechanism has the auction participants reveal their real valuation function, as this is the only dominant bidding strategy [9]. Although many of game theoretic approaches exist in literature, most of them are not transferable to practicable auction processes.…”
Section: Problems With the Combinatorial Auctionmentioning
confidence: 99%